Relação entre as propriedades físicas dos reservatórios e os traços funcionais da ictiofauna - Rodrigues , Janã Pires (2019)
The fishes are among the most affected by dams. Losses from the fish’s assemblage may be irreversible, directing the construction of new standards. Litle is known about the influence of the physical characteristics of dams in the fish’s assemblage. This characteristics change according to localization of the dam in the hydrographic basin, operation mode and purpose. So, our hypothesis is the functional structure of fishes assemblages is associated with the physical, hydrological and operational characteristics of the dam and reservoir where they inhabit. The fishes were collected in eighteen reservoirs of five hydrographic basins in the Paraná state using gill nets exposed for 24 hours, with samples in all shifts. The species have had their functionals traits classified according to literature and measures in the individuals collected. Have been analysed the physical variables: age, hydrographic basin, area of reservoir, kind of operation, area of drainage and the presence of upstream reservoir. Have been used the analyse RLQ and fourthcorner. The RLQ supplies coefficients of the directs relations between the physicals variables of R and the functionals traits of Q of the assemblage, pondered by the abundance of the species of L, and showing the relation between R and Q. The fourthcorner completes the RLQ when testing the associations between each environmental variable and functional trait individually. The results indicated that the reservoirs with similar physical characteristcs presented a functional standart of the fish’s assemblage, evidencing that the functional strutcture of the fish’s assemblage is determined, partially, for the kind of the reservoir and the kind of operation. The implantation of reservoir without consideratation of the biota, can compromise many ecosystem services, causing an environmental liability for future generations. The determination of building characteristics and the kind of operation of the dam have a huge ecological importance for the dammed environment, and yours effects should not be neglected.